A content service deployment plan for metaverse museum exhibitions—Centering on the combination of beacons and HMDs. Issue 1 (February 2017) - Choi, Hee-soo; Kim, Sang-heon
Highlights: While focusing on visitors' museum experience, new display methods to provide exhibition content in ways that allow visitors to better understand artifacts on display. The lack of interaction with visitors and the use of lighting that clearly separates real and virtual spaces have made museums inadequate as experiential spaces. To resolve those problems, this article suggests a plan to deploy content services for visitors' museum experiences by combining beacons and HMDs. This study establishes the concept of a service, which provides a virtual world experience by connecting a beacon installed in real space, that is, an exhibition room, to an HMD. Ultimately, this article presents the exhibition content thus created as experienced Metaverse made through an effective combination of AR and a virtual world. Abstract: Today, methods of museum exhibition are rapidly changing. While focusing on visitors' museum experience, new display methods employ a variety of digital technologies to provide exhibition content in ways that allow visitors to better understand artifacts on display. However, the majority of such methods rely on one-way means of delivering information. The lack of interaction with visitors and the use of lighting that clearly separates real and virtual spaces have made museums inadequate as experiential spaces. To resolve those problems, this article suggests a plan to deploy content services for visitors' museum experiences by combining beacons and HMDs. This study establishes the concept of a service, which provides a virtual world experience by connecting a beacon installed in real space, that is, an exhibition room, to an HMD (head-mounted display). Furthermore, the service also incorporates a storytelling feature to diversify user experience by presenting the characteristics of and stories about artifacts. The service design will make both online and on-site museum experiences meaningful. Ultimately, this article presents the exhibition content thus created as Metaverse exhibition content made through an effective combination of augmented reality and a virtual world.